2019
DOI: 10.1016/j.jhep.2019.03.014
|View full text |Cite|
|
Sign up to set email alerts
|

Macrophage p38α promotes nutritional steatohepatitis through M1 polarization

Abstract: Macrophages M1 polarization Hepatocytes Lipid accummulation inflammatory response p38α Steatohepatitis TNFα CXCL10 IL-6 Highlights p38a expression is increased in livers of human patients with non-alcoholic fatty liver diseases. Macrophage p38a induces experimental steatohepatitis. Macrophage p38a causes M1 macrophage polarization. p38a deleted macrophages attenuate steatohepatitic changes in hepatocytes. Pharmacological p38 inhibitors prevent steatohepatitis in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
97
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 135 publications
(112 citation statements)
references
References 31 publications
(44 reference statements)
4
97
1
Order By: Relevance
“…Zhang et al recently reported that the deletion of hepatocyte p38a exacerbated steatosis in HFD‐fed mice. ( 16 ) Surprisingly, in their study, WT and p38a Hep‐/‐ mice gained 7 to 11 g body weight after 12‐week HFD feeding, which is much lower than the typical body weight gain (~20 g) after 12‐week HFD feeding, as observed in our study. Moreover, Zhang et al reported that p38a Hep‐/‐ mice gained much more body weight than WT mice (11 versus 7 g) after 12‐week HFD feeding.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…Zhang et al recently reported that the deletion of hepatocyte p38a exacerbated steatosis in HFD‐fed mice. ( 16 ) Surprisingly, in their study, WT and p38a Hep‐/‐ mice gained 7 to 11 g body weight after 12‐week HFD feeding, which is much lower than the typical body weight gain (~20 g) after 12‐week HFD feeding, as observed in our study. Moreover, Zhang et al reported that p38a Hep‐/‐ mice gained much more body weight than WT mice (11 versus 7 g) after 12‐week HFD feeding.…”
Section: Discussioncontrasting
confidence: 88%
“…( 15 ) With regard to lipid metabolism, a recent study demonstrated that liver‐specific p38α knockout mice were more susceptible to HFD‐induced obesity and steatosis accompanied by reduced fatty acid (FA) β‐oxidation. ( 16 ) FA β‐oxidation is mainly controlled by peroxisome proliferator‐activated receptor alpha (PPARα), a ligand‐activated transcription factor that is highly expressed in the liver where FA is actively oxidized. ( 17,18 ) PPARα activity is known to be controlled by many factors and signaling pathways, including p38α, which has been shown to phosphorylate and activate PPARα in cardiac myocytes.…”
mentioning
confidence: 99%
“…Nonalcoholic fatty liver disease (NAFLD) has recently emerged as a significantly public health issue because of its high prevalence (1)(2)(3). NAFLD is characterized by a wide spectrum of liver phenotypes ranging from simple steatosis to nonalcoholic steatohepatitis (NASH) (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%
“…Nonalcoholic fatty liver disease (NAFLD) has recently emerged as a significantly public health issue because of its high prevalence (1)(2)(3). NAFLD is characterized by a wide spectrum of liver phenotypes ranging from simple steatosis to nonalcoholic steatohepatitis (NASH) (1)(2)(3). The most important clinical challenge in NASH is the progression to liver fibrogenesis, which may gradually develop to cirrhosis and eventually to hepatocellular carcinoma (HCC) (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation